2021
DOI: 10.1002/anie.202015462
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Role Reductase from Phytosterols Catabolism Enables the Efficient Production of Valuable Steroid Precursors

Abstract: 4-Androstenedione (4-AD) and progesterone (PG) are two of the most important precursors for synthesis of steroid drugs,h owever their current manufacturing processes suffer from low efficiency and severe environmental issues.In this study,wedecipher adual-role reductase (mnOpccR) in the phytosterols catabolism, whiche ngages in two different metabolic branches to produce the key intermediate 20hydroxymethyl pregn-4-ene-3-one (4-HBC) through a4-e reduction of 3-oxo-4-pregnene-20-carboxyl-CoA (3-OPC-CoA) and 2-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…The accumulation of C19 steroids in the Hsd4A and/or FadA5 deficiency strains indicates incomplete blockage of the C19 steroid pathway. Similar results have been previously reported [ 3 , 28 ]. An Hsd4A2 was testified to be dominant in M. neoaurum CCTCC AB2019054 rather than Hsd4A [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The accumulation of C19 steroids in the Hsd4A and/or FadA5 deficiency strains indicates incomplete blockage of the C19 steroid pathway. Similar results have been previously reported [ 3 , 28 ]. An Hsd4A2 was testified to be dominant in M. neoaurum CCTCC AB2019054 rather than Hsd4A [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have been previously reported [ 3 , 28 ]. An Hsd4A2 was testified to be dominant in M. neoaurum CCTCC AB2019054 rather than Hsd4A [ 28 ]. A protein in M. neoaurum DSM 44074 of 98.67% identity with Hsd4A2 in M. neoaurum CCTCC AB2019054 was found by blastp, indicating Hsd4A2 existing in M. neoaurum DSM 44074.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have been previously reported. Analysis of the M. neoaurum CCTCC AB2019054 genome revealed that there were 6 proteins with > 38% identity and 10 proteins with 31-38% identity to Hsd4A, which may compensate for its function [30]. The most identical gene, hsd4A2 (45% identity to hsd4A), was deleted, and fermentation analysis revealed that it can indeed produce 4-HBC at a signi cantly increased ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The development of effective methods for biotechnological production of steroid precursors with a carbonyl group at C‐20 is an urgent task. In particular, pregn‐4‐en‐3‐one‐20‐carbaldehyde (20‐POA) was used for the synthesis of progesterone – one of the most demanded steroid drugs 32 . Recently 20‐POA was synthesized as an intermediate in multiple reactions for production of an active pharmaceutical ingredient ursodeoxycholic acid 33 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, pregn-4-en-3-one-20-carbaldehyde (20-POA) was used for the synthesis of progesteroneone of the most demanded steroid drugs. 32 Recently 20-POA was synthesized as an intermediate in multiple reactions for production of an active pharmaceutical ingredient ursodeoxycholic acid. 33 In general, the production of aldehydes, which are predetermined for many industrial uses, brings specific challenges to biocatalytic processes and has led to a combination of in vitro and in vivo strategies for both, bulk and fine production.…”
Section: Introductionmentioning
confidence: 99%